A review of the genus Baiocis Browne, 1962 (Coleoptera: Curculionidae: Platypodinae), with new species, new synonymy and a key to males - Beaver, Roger A.; Liu, Llan-Yu (Zootaxa, 2018)
Six new species of Baiocis Browne, 1962 are described: Baiocis crassiventris Beaver & Liu, B. laosi Beaver & Liu, B. orientalis Beaver & Liu, B. spicatus Beaver & Liu, B. spiniventris Beaver & Liu, B. sumatranus Beaver & Liu, all from the Oriental region. Of the twenty species listed by Wood and Bright (1992) in the genus Baiocis, the following species belong in Crossotarsus Chapuis, 1865: imitatrix Schedl, 1973, kuntzeni (Schedl, 1937) (comb. n.); the following in Platypus Herbst, 1793: angusticeps Schedl, 1942, perangustus Schedl, 1942, seminitens Schedl, 1971, variolosus Schedl, 1942; the following in Treptoplatypus Wood, 1993: pasohensis (Schedl, 1939). The following new synonymy is proposed: Baiocis pernanulus (Schedl, 1935) (=Platypus annularis Schedl, 1975 syn. n.; =Baiocis solomonicus Browne, 1986 syn. n.); Platypus perangustus Schedl, 1942 (= Platypus sindorae Browne, 1980 syn. n.); Platypus transformis Schedl, 1936 (=Platypus angusticeps Schedl, 1942 syn. n.). Lectotypes are designated for Baiocis incisus (Sampson, 1927), and B. sublunaris (Schedl, 1937), and both sexes of the former species are redescribed. A key is given to the males of fifteen species of Baiocis. Two further species are known only from the female.